A dual-optical sensor for mancozeb by UCNP@PVP@MnO2 nanozyme. (30th May 2023) - Chen, Yinyin; Wang, Xini; Liu, Hong; Yang, Jianqing; Feng, Dongju; Hou, Kai; Wang, Xianxiang; Wu, Wei
Highlights: Up-conversion nanozyme NaYF4 :Yb/Er@PVP@MnO2 (UCNP@PVP@MnO2 ) was prepared. The combination of up-conversion fluorescence of NaYF4 :Yb/Er with enzyme-mimicking properties of MnO2 has been utilized. A fluorescent and colorimetric dual-signal mode based on nanozyme for the detection of mancozeb. Abstract: In this work, a fluorescence/colorimetric dual-mode detection method based on MnO2 nanoflower-decorated upconversion nanoparticles: NaYF4 :Yb/Er@polyvinylpyrrolidone@MnO2 (UCNP@PVP@MnO2 ) was proposed to detect the presence of mancozeb (MB). In this detection system, the MnO2 nanoflowers in the nanocomplex of UCNP@PVP@MnO2 would quench the fluorescence of the UCNP. With the addition of H2 O2 and 3, 3′, 5, 5′-tetramethylbenzidine (TMB), the reaction between MnO2 and H2 O2 resulted in the dissolution of MnO2 and the dissolution of the MnO2 layer contributed to the fluorescence recovery of UCNP. Simultaneously, MnO2 oxidized the colorless TMB to a blue product oxidized 3, 3′, 5, 5′-tetramethylbenzidine (oxTMB). The blue solution was able to quench the recovered fluorescence of UCNP due to the fluorescence inter filter effect (IFE) between the UCNP and blue oxTMB. Finally, with the addition of MB, the oxTMB was reduced to TMB by MB and the color of the solution became lighter while the fluorescence intensity of the solution increased. The detection method had a good linear range of 5–120 μM and 0.5–60 μM for fluorescence and colorimetric detection, respectively, and the limits of detection (LOD) were 2.34 and 0.245 μM, respectively.